'Actinomyces provencensis' sp. nov., 'Corynebacterium bouchesdurhonense' sp. nov., 'Corynebacterium provencense' sp. nov. and 'Xanthomonas massiliensis' sp. nov., 4 new species isolated from fresh stools of obese French patients. (July 2017) - Ndongo, S.; Andrieu, C.; Fournier, P.-E.; Lagier, J.-C.; Raoult, D.
Abstract: We report the main characteristics of ' Actinomyces provencensis ' strain SN12 T sp. nov., ' Corynebacterium bouchesdurhonense ' strain SN14 T sp. nov., ' Corynebacterium provencense ' strain SN15 T sp. nov. and ' Xanthomonas massiliensis ' strain SN8 T sp. nov., which were all isolated from stool samples from obese French patients.